The Scottish independence referendum : constitutional and political implications - McHarg, Aileen; Mullen, Tom (Thomas John); Page, Alan (Alan C.); Walker, Neil, 1960- (Oxford : Oxford University Press, 2016)
Providing a comprehensive analysis of the historical events leading up to the Scottish referendum, the referendum process, and the key issues arising out of the debate, this edited collection looks to the past and future to examine the implications of the referendum for the future of Scottish governance and the UK constitution.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 14, 2016).
Keywords: Referendum -- Scotland -- History -- 21st century; Self-determination, National -- Scotland -- History -- 21st century; Scotland -- History -- Autonomy and independence movements; Politics and Government; Politics & government